(untitled) (Medical Forum Monthly, 2024)
Objectives: In present study, the effects of insulin on the volume, absolute and relative weight of liver was studied in Wistar albino rats for a period of 4 weeks. Study Design: Retrospective / observational study. Place and duration of study: This study was conducted in the Animal House of DUHS and it took 8 months 1st June 2011 to 1st Feb 2012 to be completed. Materials and Methods: The Male Wistar albino rats which were randomized into 3 groups; each group containing 10 rats. Group A served as control, Group B as insulin treated and Group E as untreated diabetic rats. All the other rats except the Group A were kept on in-house prepared High Fat Diet (HFD) throughout the study. After 2 weeks of exclusive HFD, diabetes was induced by intraperitoneal (IP) injection of low dose streptozocin (STZ 3.5mg/100gm). After the induction, one group was left untreated (Group E) and one group (Group B) was treated with insulin for 4 weeks. The rats were then, sacrificed, liver was isolated, weighed, and its dimensions were noted. Results: The mean absolute liver weight (ALW) of rats was observed as 8.60 ± 2.54 gm, 13.18 ± 0.68 gm and 9.40 ± 3.18 gm in control, untreated and insulin treated groups respectively. And the mean percent liver weight (PLW) was calculated as 2.99 ± 0.66%, 5.10 ± 0.73% and 3.99 ± 1.37% in control, untreated and insulin treated groups respectively. Statistically significant difference was noted between ALW, PLW and liver volume of rats of the three groups. Conclusion: Insulin decreases the volume, absolute and relative weight of liver of diabetic rats when used for a short period.